Career Placement of Skilled Migrants in the U.S. Labor Market : A Dynamic Approach - Neagu, Ileana Cristina (2012)
The initial occupational placements of male immigrants in the U.S. labor market vary significantly by country of origin even when education and other factors are taken into account. Does the heterogeneity persist over time? Using data from the 1980, 1990, and 2000 U.S. Censuses, this study finds that the performance of migrants from countries with lower initial occupational placement levels improves at a higher rate compared with that of migrants originating from countries with higher initial levels. Nevertheless, the magnitude of convergence suggests full catch-up is unlikely. Country specific attributes are found to have less direct impact on the rate of assimilation than on the initial performance.